Tùrkijadaġy žalpy dìni achual žәne zajyrly memlekettìṇ dìni u̇stanymy = Religioznaja situacija v Turcii i religioznye verovanija v svetskoj respublike - Sabri, H. H. (Chabaršy. Dintanu serijasy, 2015)
In this article considered the religious situation in Turkey, a secular state with religious politics. Anatolian Seljuks , the Ottoman Empire , the Turkish Republic : analyzes the social and cultural patterns, national and spiritual values ; mosques, foundations, mazhabs, Islamic Institute, the Faculty of Theology. The article also emphasizes that the Turkish state as a secular state acted equally to all religions: Jews, Christians and Muslims, without any discrimination. The founder of the Republic of Turkey, Mustafa Kemal Ataturk was one of the foundations of secularism and constitutional government «of the Republic of Turkey is a secular state», he wrote. The article emphasizes that secularism and religion, freedom of conscience and religion are guaranteed in the Republic of Turkey to freely express their religious feelings. According to the author, secularism is one of the most important systems of democracy.